Induction of Labour in Advanced Abdominal Pregnancy with Fetal Demise due to Cord Round Neck: A Case Report of a Missed Diagnosis. (25th September 2018) - Mforteh, Ascensius Achuo; Tchakounte, Collince; Sama, Carlson-Babila; Eteme-Messi, Stephane; Djiognouo, Willy; Dohbit, Sama; Foumane, Pascal
Abstract : Background . There are increasing reports of term live abdominal pregnancies even though the diagnosis of abdominal pregnancy is made preoperatively only in 45% of cases which partly explains the high maternal and perinatal morbidity and mortality associated with abdominal pregnancy. Case Report . We report a rare case of misdiagnosed term abdominal pregnancy complicated by fetal demise due to cord round neck in a 29-year-old G3P2002 at 39-week and 1-day gestation. She noticed reduced fetal movements for which upon examination fetal death was diagnosed. Cervical ripening was started which eventually failed, and surgery was indicated. Findings were an abdominal pregnancy with a third-degree macerated fetus with cord round neck. She was discharged on day 8 postoperation to continue follow-up as an outpatient with regular β HCG and ultrasound checks. Conclusion . This case illustrates the need to effectively confirm an intrauterine location of a pregnancy even in a case of fetal demise and the need to monitor for cord abnormalities in advanced abdominal pregnancy being managed expectantly.